Systematic Review of Penis Captivus: Implications for Nursing Practice, Patient Education, and Psychosocial Support in Sexual Health Emergencies - Eling, Felix (MALATA SAINS INDONESIA, 2026)
Introduction: Penis captivus is a rare, distressing sexual dysfunction characterized by involuntary vaginal muscle spasm leading to temporary penile entrapment during intercourse. While medically documented, its implications for nursing practice remain underexplored. Objective: This systematic review synthesizes evidence on penis captivus to elucidate its pathophysiology, risk factors, and management, with specific emphasis on nursing assessment, intervention, and patient education. Methods: Following PRISMA 2020 guidelines, a comprehensive literature search was conducted across PubMed, Embase, Scopus, CINAHL (for nursing literature), and Google Scholar (2013–2023). Twelve studies reporting 18 cases met inclusion criteria. Data were extracted using standardized forms and quality assessed using JBI checklists. Results: Analysis revealed multifactorial etiology involving pelvic floor hypertonicity, psychological triggers (anxiety, trauma), and male factors (prolonged erection). Interventions, primarily reassurance, guided breathing, and positional changes all of which fall within nursing scope of practice. Nursing implications identified include acute psychological first aid, patient and couple education, coordination of multidisciplinary referrals, and long-term psychosocial support. Conclusion: Penis captivus, while rare, represents a legitimate sexual health emergency with significant nursing implications. Nurses in emergency, mental health, and primary care settings are uniquely positioned to provide immediate intervention, reduce patient distress, and facilitate appropriate follow-up. This review provides an evidence-based framework for nursing assessment and management, addressing a critical gap in sexual health nursing education and practice.